Desambiguação das preposições do português no livro terceiro da Clavis Prophetarum - Assunção, Carlos; Tavares, José Paulo; Fernandes, Gonçalo (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
The third book of Clavis Prophetarum (Clavis III PT), written by Father António Vieira, in its Portuguese translation published in 2000, is the corpus of this work. To be able to analyse this corpus, we need electronic language resources that are formalised in order to obtain the greatest possible coverage and to be used in appropriate systems. For the Portuguese language, we already have reliable resources, developed since the 90s by LabEL - Laboratory of Language Engineering. The main objective of this article is to develop rules of automatic disambiguation of prepositions and their syntagmata, as well as to assess the effectiveness of their application, in order to allow subsequent reliable approaches in the study of this category in the corpus using automatic techniques. The methodology used describes pari passu annotations, occurrences and the creation of electronic resources considered essential to the disambiguation process.